Comparative study of presidential elections 2017 and 2022 in Timor-Leste - Martins, Francisco Siquera; Cruz, Rui da Cruz; Martins, Leonito M. (International Journal of Global Sustainable Research, 2024)
This comparative study aims to enhance knowledge and improve future organizational performance. The 2017 President's election in Timor-Leste showed a shift in public perceptions and doubts about peace and stability. The 2022 election will determine the country's President for the next five years. The research identified a problem with the 2017 elections, which were perceived as peaceful and inclusive. The study used qualitative research methods, including primary and secondary data interviews and documentation at the research site. The results showed that the 2017 election had positive effects on peace and stability, including increased participation and amendments to the Law on the President's election. The research methodology used was qualitative, involving primary and secondary data interviews and documentation at the research site.